The Hippo pathway and p27 Kip1 cooperate to suppress mitotic regeneration in the organ of Corti and the retina - Eva Jahanshir; Juan Llamas; Yeeun Kim; Kevin Biju; Sanyukta Oak; Ksenia Gnedeva (Proceedings of the National Academy of Sciences, 2025)
The mature mammalian auditory sensory organ, the organ of Corti (OC), lacks the capacity for regenerating hair cells, leading to permanent hearing impairment. In contrast, the vestibular system has a limited capacity for hair cell regeneration, which we have shown to be further enhanced by inhibiting the Hippo pathway. Here, we demonstrate that, despite similar transcriptional responses, only vestibular and not auditory supporting cells proliferate as a result of Yap activation following Hippo inhibition. Mechanistically, we identify p27 Kip1 , a cell cycle kinase inhibitor encoded by Cdkn1b , as an additional barrier preventing cell cycle reentry specifically in the OC. We show that while in both systems Yap stimulates p27 Kip1 degradation through activation of its direct target gene Skp2 , this protein-level control is antagonized by an unusually high level of Cdkn1b transcription in the cochlea. Consequently, p27 Kip1 activity is maintained in the OC even in the presence of constitutively active Yap5SA, counteracting its mitogenic effects. Supporting this model, inactivation of the Hippo pathway in the Cdkn1b -deficient background is sufficient to induce adult auditory supporting cell proliferation in vivo. Furthermore, we show that the synergistic interaction between Hippo and p27 Kip1 is conserved in the retina where inhibition of both pathways potently induces Müller glia proliferation and initiates neuronal regeneration. Our work uncovers the molecular mechanism preventing quiescent adult sensory progenitor cells, supporting cells in the ear and Müller glia in the eye, from reentering the cell cycle after damage—the key step toward sensory receptor regeneration blocked in mammals.